Respuesta :

Answer:

Step-by-step explanation:

Step  1  :

Trying to factor by splitting the middle term

1.1     Factoring  k2-12k+23

The first term is,  k2  its coefficient is  1 .

The middle term is,  -12k  its coefficient is  -12 .

The last term, "the constant", is  +23

Step-1 : Multiply the coefficient of the first term by the constant   1 • 23 = 23

Step-2 : Find two factors of  23  whose sum equals the coefficient of the middle term, which is   -12 .

     -23    +    -1    =    -24

     -1    +    -23    =    -24

     1    +    23    =    24

     23    +    1    =    24

Observation : No two such factors can be found !!

Conclusion : Trinomial can not be factored

ACCESS MORE